Confinement in Wendelstein 7-X limiter plasmas. (14th June 2017) - Hirsch, M.; Dinklage, A.; Alonso, A.; Fuchert, G.; Bozhenkov, S.; Höfel, U.; Andreeva, T.; Baldzuhn, J.; Beurskens, M.; Bosch, H.-S.; Beidler, C.D.; Biedermann, C.; et al.
Abstract: Observations on confinement in the first experimental campaign on the optimized Stellarator Wendelstein 7-X are summarized. In this phase W7-X was equipped with five inboard limiters only and thus the discharge length restricted to avoid local overheating. Stationary plasmas are limited to low densities  <2–3 · 10 19 m −3 . With the available 4.3 MW ECR Heating core T e ~ 8 keV, T i ~ 1–2 keV are achieved routinely resulting in energy confinement time τ E between 80 ms to 150 ms. For these conditions the plasmas show characteristics of core electron root confinement with peaked T e -profiles and positive E r up to about half of the minor radius. Profiles and plasma currents respond to on- and off-axis heating and co- and counter ECCD respectively.